R-Spondin 1 (RSPO1) Increases Mouse Intestinal Organoid Unit Size and Survival in vitro and Improves Tissue-Engineered Small Intestine Formation in vivo - Levin, Gabriel; Zuber, Samuel M.; Squillaro, Anthony I.; Sogayar, Mari Cleide; Grikscheit, Tracy C.; Carreira, Ana Claudia O. (Frontiers in Bioengineering and Biotechnology, 2020)
Cell therapy and tissue engineering has recently emerged as a new option for short bowel syndrome (SBS) treatment, generating tissue engineered small intestine (TESI) from organoid units (OU) and biodegradable scaffolds. The recombinant human R-Spondin 1 (rhRSPO1) protein may be a key player in this process due to its mitogenic activity in intestinal stem cells. Aiming at optimizing the TESI formation process and advancing this technology closer to the clinic, we evaluated the effects of rhRSPO1 protein on OU culture and TESI formation. Intestinal OU were isolated from C57BL/6 mice and cultured in Matrigel in the presence or absence of recombinant human rhRSPO1. Throughout the culture, OU growth and survival rates were evaluated, and cells were harvested on day 3. OU were seeded onto biodegradable scaffolds, in the presence or absence of 5µg of rhRSPO1 and implanted into the omentum of NOD/SCID mice in order to generate TESI. The explants were harvested after 30 days, weighed, fixed in formalin and embedded in paraffin for histological analysis and immunofluorescence for different cell markers. After three days, rhRSPO1-treated OU attained a larger size, when compared to the control group, becoming 5.7 times larger on day 6. Increased survival was observed from the second day in culture, with a two-fold increase in OU survival between days 3 and 6. A 4.8-fold increase of non-phosphorylated beta-catenin and increased relative expression of Lgr5 mRNA in the rhRSPO1-treated group confirms activation of the canonical Wnt pathway and suggests maintenance of the OU stem cell niche and associated stemness. After 30 days of in vivo maturation, rhRSPO1-treated TESI presented a larger mass than constructs treated with saline, developing a more mature intestinal epithelium with well-formed villi and crypts. In addition, the efficiency of OU-loaded rhRSPO1-treated scaffolds significantly increased, forming TESI in 100% of the samples (N=8), of which 40% presented maximum degree of development, as compared to 66.6% in the control group (N=9). rhRSPO1 treatment improves the culture of mouse intestinal OU, increasing its size and survival in vitro, and TESI formation in vivo, increasing its mass, degree of development and engraftment.